The Influence Of Sales Promotion, Brand Image, And Store Atmosphere On Impulsive Buying Of Mixue Ice Cream And Tea - Siregar, Ihsan Mulia; Ratuliu, Tara (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This study aims to determine and analyze the effect of sales promotion, brand image, and store atmosphere on impulsive buying of Mixue ice cream and tea consumers in Bengkulu City. This research uses a quantitative approach with the help of Eviews 10 software for data analysis. The results of the statistical testing show that sales promotion has a positive and significant effect on impulsive buying of Mixue ice cream and Tea Bengkulu City. Brand image positively and significantly affects impulsive Mixue ice cream and Tea Bengkulu City buying. Store Atmosphere also positively and significantly influences impulsive buying of Mixue ice cream and Tea Bengkulu City. Then, simultaneously, sales promotion, brand image, and store atmosphere positively and significantly affect the impulsive buying of Mixue ice cream and Tea Bengkulu City. The results of this study are expected to be beneficial for related parties, especially Mixue ice cream and Tea companies, to continue to improve and maintain the factors that influence impulsive buying of Mixue ice cream and Tea consumers in Bengkulu City.